Wildness and Wild Spaces in Residential Yards: Changing Neighborhood Norms to Support Pollinator Populations - Andrea K. Burr (MDPI AG, 2021)
Insect pollinator populations, critical to the global food supply, are declining. Research has found robust bee communities in cities, which are supported by diverse urban habitat and foraging resources. Accounting for 35–50% of urban green space, U.S. private residential yards can serve as important forage and nesting sources for pollinators. Incorporating wild attributes and wildness, such as native vegetation and less intensive yard-management practices, is key. However, urban vegetation, and its effects on local native bee populations, is shaped by social and cultural preferences, norms, aesthetics, values, and identities. The perfect lawn ideal of a highly manicured turfgrass yard dominates neighborhood landscapes and is often at odds with the habitat needs of pollinators. As part of a three-year study investigating the sociocultural drivers of residential vegetation choices in St. Louis, MO, USA, we interviewed 85 decisionmakers in order to understand choices about private residential yard maintenance. This paper presents an emergent finding concerning how residents conceptualize and talk about the urban-yard aesthetic, using the terms “wild” and “wildness”, which reflect a range of levels in the demand for urban wild spaces in their neighborhoods. The discourse of wildness offers a nontechnical route for understanding the connections between the ecological consequences of urbanization, with human attitudes towards nature that shape the biological functioning of human-generated habitats.